Interaction between biofilm growth and NAPL remediation: A pore-scale study. (March 2019) - Benioug, M.; Golfier, F.; Fischer, P.; Oltean, C.; Buès, M.A.; Yang, X.
Highlights: A complex and sophisticated mathematical model at the pore scale has been developed for simulating biofilm growth, fluid flow, and the dissolution of immobile non-aqueous-phase-liquids (NAPLs). A series of numerical simulations were conducted to investigate the mechanisms involved in the enhanced dissolution of the NAPLs due to microbial activity. The model can be used to validate assumptions which are typically invoked to simplify upscaling of NAPL dissolution to larger scales. Abstract: In this paper, we introduce a pore-scale model to study the interaction between biofilm growth and non-aqueous-phase-liquid (NAPL) dissolution. Liquid flow and dissolved NAPL transport are coupled with a biofilm growth model to correctly describe the complex dynamics of the processes including fluid flow, NAPL dissolution/biodegradation and biofilm growth. Fluid flow is simulated using an immersed boundary-lattice Boltzmann (IB-LB) model; while solute transport is solved by a cut-cell finite volume method (FVM). A uniform dissolution approach is also adopted to capture the temporal evolution of trapped blobs. Spatio-temporal distributions of the biomass are investigated using a cellular automaton algorithm combined with the immersed boundary method (IBM). Simulations focused on NAPL dissolution in both abiotic and biotic conditions are conducted to assess the capability of the model. In abiotic conditions, we analyze the effects of the hydrodynamic regimes and the spatial distribution of NAPL blobs on the dissolution rate under different assumptions ( i.e., blob size and Péclet number). In biotic conditions, a series of impact factors are also investigated ( i.e., spatial distribution, reaction kinetics and NAPL-induced toxicity). Finally, the current model is used to evaluate the pore scale relevance of a local equilibrium assumption between fluid phase and biofilm phase in the vicinity of the NAPL source.